Standarisasi dan Perbaikan Proses Bisnis dengan Pendekatan Business Process Improvement Pada Viseworks Studio - Afif, Arkan Muhammad; Prasetyo, Aries Heru (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2021)
Viseworks Studio is a pre-startup company running on digital art sector of creative industry that offers complete digital asset for visual branding and utility purpose such as: graphic design, photography, videography, animation, interior and architecture, and interaction design. In a new established company, there is no well-standardized business process that causes business cannot run maximally because it is still exploring what kind of activity that must be done and what must be avoided. With the existence of business process standardization and improvement, hopefully company can run the business effectively, efficently, and be able to create added value for customers. This research contains of qualitative data gathered from interview, experiment, and observation directly to the subject that is focused on the people, process, and technology aspect. The result of business process standardization and improvement are: gain of speed from the machine and waiting time, gain of quality, increase of product variety, and gain of product value. Although there has been an improvement, business process lifecycle must be running over the time to create improvement continuously.